PEMILIHAN SUPPLIER SEMEN PADA CV. RIZKI JAYA ABADI DI KABUPATEN MOJOKERTO MENGGUNAKAN METODE FUZZY AHP (ANALYTICAL HIERARCHY PROCESS) - Satrio Pinandito Tunggal Talangkas; Farida Pulansari (Tekmapro : Journal of Industrial Engineering and Management, 2021)
One of the important activities in business that can affect business competitiveness is the process of procuring goods or services. The existence of alternative suppliers is often the main problem for business owners. The problem arises when these suppliers have several quality differences in the criteria previously determined by the company. In these conditions the business owner must be able to choose the best supplier to supply goods or services needed by his business. CV. Rizki Jaya Abadi is a construction service company which has several branches. One way to ensure that customer demands are met is to ensure that the building materials used are of good quality or suitable for their purpose. One of the main building materials is cement. In solving these problems, the researchers used the Fuzzy Analythical Hierarchy Process (FAHP) method. This research shows that there are 5 main criteria in choosing cement suppliers, namely Price, Quality, Delivery, Response, and Service. From the calculations performed, it was found that the best cement supplier ranking for CV. Rizki Jaya Abadi respectively is UD. Hana Jaya with a value of 0.2479, UD. Pododadi with a value of 0.2183, UD. Murah Jaya with a value of 0.1933, UD. Stone with a value of 0.1749, and UD. Sari Agung with a value of 0.1655.